Hubungan Pengetahuan Lingkungan dengan Sikap Peduli Lingkungan pada Siswa SMP Negeri 40 Samarinda - Putriyanni Putriyanni; Vandalita Maria Magdalena Rambitan; Ruqoyyah Nasution; Suparno Putera Makkadafi; Masitah Masitah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to determine the relationship between environmental knowledge and environmental awareness among students of SMP Negeri 40 Samarinda. Awareness of the importance of protecting the environment needs to be instilled from an early age through increasing knowledge and developing environmental awareness among students. Lack of environmental awareness, such as littering and not maintaining school cleanliness, shows the importance of environmental knowledge in developing students' environmental awareness. This study was conducted to examine the relationship between environmental knowledge and environmental awareness among students of SMP Negeri 40 Samarinda. This study used a quantitative approach with a correlational method. Data collection was carried out through questionnaires given to students as research respondents. The data obtained were analyzed using normality tests and correlation hypothesis tests. The results showed that the data were normally distributed. Based on the results of the hypothesis test, a correlation coefficient value of 0.345 was obtained, which is included in the low category, thus indicating a low positive relationship between environmental knowledge and students' environmental awareness. This positive relationship indicates that the higher the students' environmental knowledge, the better the environmental awareness they have. However, the low correlation value indicates that environmental knowledge does not fully influence students' environmental awareness, as other factors contribute, such as habits, the surrounding environment, and the inculcation of environmentally conscious behavior in daily life. Therefore, supporting efforts through environmental education and programs in schools are needed to optimally develop students' environmental awareness and attitudes.